PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF MRSA AMONG PEDIATRICS AND YOUNG ADULT PATIENTS (Journal of Medical & Health Sciences Review, 2026)
Introduction: Staphylococcus aureus is a grampositive bacteria which causes various infections both in children and adults. Methicillin-resistant strains (MRSA) are a major health risk because they are resistant to antibiotics, mostly because of changes in β-lactamase enzymes and penicillin-binding proteins.Objective: To determine the prevalence of MRSA infection in Pediatric and youngAdult patients and to study the antibiotics susceptibility pattern of MRSA among the isolates from population.Methodology: A cross-sectional study using convenience sampling was conducted in Rawal General Hospital Rawalpindi. The study size include total 107 participants divided in 2 groups children (0-12 years) and young adults (12-30 years), Samples were examined using microbiological techniques, including bacterial culture, Gram staining, and biochemical tests. Antibiotic susceptibility testing was carried out using the Kirby-Bauer method. Data analysis was done through SPSS software version 25.Result: Our study showed high MRSA prevalence in children with higher rates in females. MRSA was common in blood specimens of children and pus specimens of adults. Staphylococcus aureus in adults and paeds showed highest sensitivity to cefoxitin (100%) tigecycline, chloramphenicol, and linezolid. High resistance was observed to penicillin and erythromycin in both groups. MRSA isolates in adults and pediatric patients showed 100% resistance to cefoxitin, confirming methicillin resistance. High resistance was observed to penicillin, ciprofloxacin, and erythromycin, while linezolid, chloramphenicol, and doxycycline showed notable sensitivity. These findings highlight limited antibiotic options, with linezolid and chloramphenicol emerging as the most effective treatments.Conclusion: Our study shows a higher prevalence of MRSA in children, especially around 1 month of age, and more in females. In adults, pus was the main source, while in children it was blood. Doxycycline was more effective in adults. Linezolid and chloramphenicol were effective in both groups.